Acute Endoplasmic Reticulum Stress Induces Inflammation Reaction, Complement System Activation, and Lipid Metabolism Disorder of Piglet Livers: A Proteomic Approach - Wang, Xiaohong; Xin, Hairui; Xing, Mingjie; Gu, Xianhong; Hao, Yue (Frontiers in Physiology, 2022)
Endoplasmic reticulum stress (ERS) is closely associated with the occurrence and development of many liver diseases. ERS models mostly include experimental animals such as rats and mice. However, pigs are more similar to humans with regards to digestion and metabolism, especially liver construction, yet few reports on ERS in pigs exist. In order to explore changes in the liver under ERS, we used tunicamycin (TM), which can cause liver jaundice and damage liver function, to establish acute ERS models in piglets using a low TM dosage (LD, 0.1 mg/kg body weight (bw)), high TM dosage (HD, 0.3 mg/kg bw), or vehicle for 48 h. We found that both LD and HD induced ERS, as verified by the ERS-linked proteins. Furthermore, the concentrations of proinflammatory cytokines TNF-α  and IL-6 were elevated in TM-treated piglet livers, and the plasma levels of IL-6 and CRP were also higher, indicating the occurrence of inflammation in TM-treated piglets. The complement system was activated in TM-treated piglets, as indicated by increased levels of complement factors and activation products C3, C5a, and AP50. In order to gain insight into the global changes in liver proteins under ERS, we performed an isobaric tags for relative and absolute quantitation (iTRAQ)-based proteomic analysis on the livers of HD- and vehicle-treated piglets. Proteomic analysis identified 311 differentially expressed proteins (DEPs) between the two groups, and a Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis suggested that the DEPs were mainly enriched in signaling pathways such as metabolic pathways, protein processing in the endoplasmic reticulum, and complement and coagulation cascades. Many proteins involved in protein folding, lipid transport, and oxidation were upregulated. Proteins involved in lipid synthesis were downregulated to alleviate liver steatosis, and most complement factors were upregulated to protect the body, and Pearson correlation analysis found that most of DEPs in complement and coagulation pathway were significantly correlated with plasma CRP, IL6 and AP50. Our results revealed that TM can activate ERS, marked by liver injury and steatosis, inflammatory reactions, and complement activation in piglets.